2012
DOI: 10.1051/0004-6361/201219242
|View full text |Cite
|
Sign up to set email alerts
|

The energy of waves in the photosphere and lower chromosphere

Abstract: Context. The energy source powering the solar chromosphere is still undetermined, but leaves its traces in observed intensities. Aims. We investigate the statistics of the intensity distributions as a function of the wavelength for Ca ii H and the Ca ii IR line at 854.2 nm to estimate the energy content in the observed intensity fluctuations. Methods. We derived the intensity variations at different heights of the solar atmosphere, as traced by the line wings and line cores of the two spectral lines. We conver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 99 publications
(102 reference statements)
1
19
0
Order By: Relevance
“…), researchers attempted to probe the energetics of magnetoacoustic waves further still by harnessing the improved spatial and/or temporal resolutions on offer. However, each time (Fossum & Carlsson 2005a, 2006Beck et al 2009;Bello González et al 2009Beck et al 2012Beck et al , 2013a the authors were unable to conclusively verify that these wave modes carry sufficient energy to play a dominant role in atmospheric heating. Perhaps, as highlighted by the work of Jefferies et al (2006), Wedemeyer-Böhm et al (2007), Kalkofen (2007Kalkofen ( , 2008, to name but a few, we still require yet higher spatial and temporal resolutions to be able to accurately constrain the rapid fluctuating dynamics synonymous with propagating magnetoacoustic wave modes in small-scale magnetic elements.…”
Section: Quiet Sun and Network Locationsmentioning
confidence: 97%
“…), researchers attempted to probe the energetics of magnetoacoustic waves further still by harnessing the improved spatial and/or temporal resolutions on offer. However, each time (Fossum & Carlsson 2005a, 2006Beck et al 2009;Bello González et al 2009Beck et al 2012Beck et al , 2013a the authors were unable to conclusively verify that these wave modes carry sufficient energy to play a dominant role in atmospheric heating. Perhaps, as highlighted by the work of Jefferies et al (2006), Wedemeyer-Böhm et al (2007), Kalkofen (2007Kalkofen ( , 2008, to name but a few, we still require yet higher spatial and temporal resolutions to be able to accurately constrain the rapid fluctuating dynamics synonymous with propagating magnetoacoustic wave modes in small-scale magnetic elements.…”
Section: Quiet Sun and Network Locationsmentioning
confidence: 97%
“…Fossum & Carlsson (2005), Cuntz, Rammacher & Musielak (2007), Kalkofen (2007) and Bello González et al (2009). Recent joint observational and theoretical studies aimed at elucidating the significance of wave heating in the solar photosphere and lower chromosphere were given by Beck & Rammacher (2010), E-mail: diaa.gadelmavla@izmirekonomi.edu.tr (DEF); cuntz@uta.edu (MC); wrammacher@online.de (WR) Beck, Rezaei & Puschmann (2012) and Wedemeyer-Böhm et al (2012). The latter study investigates the channelling of magnetic energy through the solar chromosphere into the corona, thus resembling super-tornadoes under solar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…a time series of about one-hour duration and a large-area map (cf. Beck et al 2009Beck et al , 2012BE09 and BE12 in the following). The other three data sets are large-area maps of the active region NOAA 10978 (cf.…”
Section: Relevant Observational Detailsmentioning
confidence: 99%
“…2) reach about 1000 K at log τ ∼ −4 (z ∼ 700 km). Beck et al (2012;BE12) found a pronounced difference in the skewness of intensity distributions between field-free and magnetic locations, i.e. an increased skewness on magnetic locations at intermediate wavelengths between the line wing and the core, corresponding to formation heights of about z = 135−150 km.…”
Section: Average Temperature and Temperature Statistics In Qsmentioning
confidence: 99%